The influencing factors of public communication behavior for public health emergencies - Liu, Jie; Hashim, Norliana; Syed Zainudin, Sharifah Sofiah; Mohammad Razi, Siti Aishah (Human Resource Management Academic Research Society, 2023)
This study aims to provide a comprehensive understanding of public communication behavior and to analyse the influence factors of communication behavior on public health emergencies. The study reviews the previous literature on public communication behavior and the influence factors of communication behavior during health emergencies and proposes a conceptual model of public communication behavior in health emergencies. The findings of this study demonstrate that the factors influencing public communication behavior during health emergencies can be broadly classified into four categories, risk perception, emotion, public recognition, and motivation. The proposed conceptual model of public communication behavior provides a theoretical integrated overview to understand the relationships between these factors and public communication behavior in health emergencies. Furthermore, this study analyses public communication behavior from the public's internal communication perspective, which has not been adequately explored in previous research. The literature review adds to the body of knowledge by introducing four main groups of factors affecting communication behavior during health emergencies and highlights the importance of understanding the factors that influence communication behavior to improve communication effectiveness. This study is significant for understanding public health information communication behavior in health emergencies and providing government and organisations with high-quality guidance.